The wonderful X-stitching mobile application - Chua, Jiayi (Nanyang Technological University, 2023)
This report explores the integration of modern technology into the enduring tradition of cross-stitch, which has spanned centuries. The focus of the paper is on the development of a user-friendly mobile application designed for cross-stitch enthusiasts of all skill levels. Utilising Android Studio and employing design thinking methodology, the application offers a range of features, including colour identification from images, matching thread colours, and step-by-step instructions for cross-stitching. The aim is to make cross-stitching more accessible by providing a seamless and informative experience for users, ultimately fostering a broader appreciation for this timeless craft.